Flavonoid content analysis of ethanol extract of kluwih (Atrocarpus camansi) fruit seeds by UV-Vis spectrophotometry - Rahmawati, Rahmawati; Muflihunna, Andi; Sarmila, Sarmila (Pharmaceutical Reports, 2025)
Kluwih is traditionally used to lower cholesterol levels, blood pressure and help treat diabetes. Kluwih (Arocarpus camansi) is one of the plants that contains various types of secondary metabolites such as alkaloids, phenolics, steroids, and flavonoids. The content of these metabolites plays a major role in its pharmacological activities. This study aims to determine the flavonoid levels contained in the ethanol extract of kluwih fruit seeds (Atrocarpus camansi). This study used UV-Vis spectrophotometric method with potassium acetate reagent 120Mm and aluminum chloride 2% to form a yellow color solution and as a comparison used quercetin. The results showed that the average flavonoid content of ethanol extract of kluwih fruit seeds (Atrocarpus camansi) was 6.750 mg ± 1.35 QE/g extract.